Implementation Science of Pre-exposure Prophylaxis: Preparing for Public Use - Underhill, Kristen (2010)
As efficacy trials of antiretroviral pre-exposure prophylaxis (PrEP) continue, a growing literature has begun anticipating the potential challenges of implementing PrEP for HIV prevention. These efforts coincide with a shift toward combination interventions for preventing HIV, which integrate biomedical, behavioral, and structural components. The optimal implementation of PrEP would exemplify this combination model, incorporating not only PrEP drugs, but also HIV testing, safety screening, behavioral interventions addressing adherence and risk behavior, and long-term monitoring. Efforts to plan for PrEP implementation therefore present an opportunity to advance the science of implementation and delivery in HIV prevention, in order to better address the challenges of scaling up combination approaches. We review the published and unpublished literature on PrEP implementation, organizing themes into five categories: scientific groundwork, regulatory and policy groundwork, stakeholder and infrastructure groundwork, delivery, and long-term monitoring. The lessons from PrEP planning can benefit the scale-up of future combination interventions.